2004
DOI: 10.1016/j.tvjl.2003.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Viability of equine articular chondrocytes in alginate beads exposed to different oxygen tensions

Abstract: Ischaemia and reperfusion are suspected to alter chondrocyte metabolism. Here, we studied the effects of three oxygen (O 2 ) tensions on the viability of equine articular chondrocytes isolated from the cartilage of the distal interphalangeal joint of horses. Chondrocytes were cultured in alginate beads under 1%, 5% or 21% gas phase O 2 concentration for 14 days, cellular growth kinetics were measured (n = 6), and the cells were observed by light microscopy after staining for necrotic and apoptotic cell detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…At 0 g/L glucose, the number of cells decreased whatever the O 2 tension was, but the decrease reached statistical significance only for 21% O 2 tension. These observations confirmed our previous results demonstrating the capacity of the chondrocytes cultured in alginate beads to survive at different O 2 tensions until at least eight days of culture (Schneider et al, 2004) and the results of the new study of the mature equine articular chondrocytes in alginate beads during 11 days with different O 2 and glucose concentrations (Fig. 6).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…At 0 g/L glucose, the number of cells decreased whatever the O 2 tension was, but the decrease reached statistical significance only for 21% O 2 tension. These observations confirmed our previous results demonstrating the capacity of the chondrocytes cultured in alginate beads to survive at different O 2 tensions until at least eight days of culture (Schneider et al, 2004) and the results of the new study of the mature equine articular chondrocytes in alginate beads during 11 days with different O 2 and glucose concentrations (Fig. 6).…”
Section: Discussionsupporting
confidence: 91%
“…In another study, we demonstrated that the intracellular ATP levels were not significantly different for equine chondrocytes cultured in alginate beads for eight days with 4.5 g glucose/L, at 1%, 5% or 21% O 2 as regulated in the gas phase, suggesting that the rate of the mitochondrial respiration did not intensively change whatever the applied O 2 tension was (Schneider et al, 2004). Furthermore, we observed a cell survival of 40-60% at 1% O 2 tension, even in the complete absence of glucose.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Articular chondrocytes in vivo live under poor oxygen (O 2 ) tension [3]. We already observed that equine articular chondrocytes in culture could survive for more than 10 days to near anoxia conditions (<1% O 2 in the surrounding atmosphere) [4], and we recently observed that the O 2 uptake of equine articular chondrocytes was very low (20.5 pmol O 2 /min/10 6 cells), even if they were cultured at 21% O 2 during 48 h before the assays. Their respiratory rate did not increase after an anoxia period of 30 min (data submitted for publication).…”
mentioning
confidence: 99%